2017
DOI: 10.3389/fmicb.2017.00473
|View full text |Cite
|
Sign up to set email alerts
|

Methylation on RNA: A Potential Mechanism Related to Immune Priming within But Not across Generations

Abstract: Invertebrate immune priming is a growing field in immunology. This phenomenon refers to the ability of invertebrates to generate a more vigorous immune response to a second encounter with a specific pathogen and can occur within and across generations. Although the precise mechanism has not been elucidated, it has been suggested that methylation of DNA is a cornerstone for this phenomenon. Here, using a novel method of analytical chemistry (a reversed-phase liquid chromatography procedure) and the beetle Teneb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 46 publications
0
28
0
Order By: Relevance
“…Nevertheless, our results indicate that such mechanisms should enable reactions that can be transferred not only within the organism (i.e., systemic reactions) but even across generations up to the F 2 . This might be helpful for narrowing down targets for further in-depth studies from the large range of candidate genes and mechanisms identified in T. castaneum (Ferro et al, 2017; Greenwood et al, 2017; Tate et al, 2017; Schulz et al, 2018) and other insect species (e.g., Castro-Vargas et al, 2017; Tassetto et al, 2017; Cime-Castillo et al, 2018; Mondotte et al, 2018). On a more cautionary note, our study also further supports the view that immune priming comprises a multitude of phenomena that might be based on diverse mechanisms among and even within species (for review see Contreras-Garduño et al, 2016; Milutinović and Kurtz, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, our results indicate that such mechanisms should enable reactions that can be transferred not only within the organism (i.e., systemic reactions) but even across generations up to the F 2 . This might be helpful for narrowing down targets for further in-depth studies from the large range of candidate genes and mechanisms identified in T. castaneum (Ferro et al, 2017; Greenwood et al, 2017; Tate et al, 2017; Schulz et al, 2018) and other insect species (e.g., Castro-Vargas et al, 2017; Tassetto et al, 2017; Cime-Castillo et al, 2018; Mondotte et al, 2018). On a more cautionary note, our study also further supports the view that immune priming comprises a multitude of phenomena that might be based on diverse mechanisms among and even within species (for review see Contreras-Garduño et al, 2016; Milutinović and Kurtz, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Long noncoding RNAs (lncRNAs) have role in the establishment of long‐lasting epigenetic modifications which are causal for trained immune response (Fok et al 2019). In a recent study, T. molitor beetle model related to immune priming reported that RNA methylation as one potential mechanism within generations only but not across generations, though survival was higher in both within and across generations (Castro‐Vargas et al 2017).…”
Section: Epigenetics and Transgenerational Innate Immune Memory In Shmentioning
confidence: 99%
“…These signals include the transfer of microbial degradation products (i.e. PAMPs) to their developing embryos to prime their immune response (Freitak et al, 2014), or via epigenetic mechanisms, such as DNA chromatin modification or small RNA, to elevate the constitutive expression of immune effector genes (Castro-Vargas et al, 2017;Norouzitallab et al, 2016). Paternal immune priming can also be transmitted by epigenetic mechanisms via the sperm or by compounds transferred with the seminal fluid (Eggert et al, 2014).…”
Section: Introductionmentioning
confidence: 99%